1999
DOI: 10.1093/jac/43.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B susceptibility testing of Candida lusitaniae isolates by flow cytofluorometry: comparison with the Etest and the NCCLS broth macrodilution method

Abstract: A flow cytofluorometric susceptibility test (FCST) was used for rapid determination of the susceptibility of Candida lusitaniae isolates to amphotericin B. The test is based on the decrease in fluorescence intensity of cells stained with 3,3'-dipentyloxacarbocyanine iodide (DiOC5(3)), a membrane potential-sensitive cationic dye, after drug treatment. A total of 58 C. lusitaniae clinical isolates including strains known to be amphotericin B-resistant on the basis of in-vivo and/or in-vitro data were tested. MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…(2,69,79,146,(161)(162)(163)(164). Staining (or lack of staining) with suitable dyes permits the rapid detection of damaged fungi.…”
Section: Flow Cytometry and Use Of Viability Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2,69,79,146,(161)(162)(163)(164). Staining (or lack of staining) with suitable dyes permits the rapid detection of damaged fungi.…”
Section: Flow Cytometry and Use Of Viability Dyesmentioning
confidence: 99%
“…Recent work has further explored this possibility (80,88,97,151,175,176,223) and shown the potential for correlation of flow cytometry-based techniques with the reference method. One study suggested that flow cytometry might be especially useful for detection of amphotericin B resistance (69). In conceptually related studies, fluorescent viability dyes have been used to examine the nature of drug-induced damage to yeasts and moulds (50, 111) and to estimate MICs and minimal fungicidal concentrations (MFCs) for molds (105).…”
Section: Flow Cytometry and Use Of Viability Dyesmentioning
confidence: 99%
“…However, this method is somewhat labor-intensive, unreliable for detection of amphotericin B resistance, and prone to the trailing-growth phenomenon with azole antifungals (9,14). Alternative methods such as spectrophotometry (1,3), colorimetry (10,12), agar-based assay (2,11), and flow cytometry (FC) (4,5,6,8,13,17) are being evaluated. The objectives of the present study were to evaluate the FC method by using isolates previously tested in another laboratory and to determine interlaboratory agreements between center 1 (C1; University of Iowa College of Medicine, Iowa City) and center 2 (C2; Mycology Laboratory, Wadsworth Center, Albany, N.Y.).…”
mentioning
confidence: 99%
“…The laboratory detection of amphotericin B-resistant strains remains problematic, notably with the widely used National Committee for Clinical Laboratory Standards (NCCLS) M27-A2 procedure (12,13). Alternatives, such as antibiotic medium 3 (AM3) with the M27-A2 method, Etest with a predefined gradient of drug concentration, Iso-Sensitest broth, and flow cytometry (FC) have been used to discriminate between amphotericin B-susceptible and -resistant strains (2,4,5,7,9,11,14). Etest with AM3 agar did not yield good results with susceptible and resistant strains, but Etest with RPMI provided reliable discrimination (9).…”
mentioning
confidence: 99%